+0  
 
+1
97
1
avatar+701 

midpoint 

http://prntscr.com/lbs8z2

 Oct 29, 2018
 #1
avatar+98044 
+1

Let ( x, y)  be  the coordinates of Q

 

Using the  mid-point formula  we have

 

x coordinate of P + x coordinate of Q 

_________________________________   =   x coordinate of  M

                     2

 

[ 11 + x ]        =       5           multiply both sides by 2

_______

      2

 

11 +  x  = 10     subtract  11 from both sides

 

x  =  -1

 

And  

 

 y coordinate of P  +  y coordinate of Q     =  y coordinate of M

_________________________________

                      2

 

[ -10  +  y  ]   =   -  2                multiply both sides by  2

___________

        2

 

-10 +   y  =  -4          add 10 to both sides

 

y   = 6

 

So.... Q =  ( x, y  )  =  ( -1 , 6 )

 

 

cool cool cool

 Oct 29, 2018

7 Online Users

avatar
avatar